2009
DOI: 10.1111/j.1471-4159.2009.05937.x
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic striatal neurons exhibit caspase‐independent, mitochondrially mediated programmed cell death

Abstract: 1These authors contributed equally to this work.Abbreviations used: [Ca 2+ ] i, intracellular calcium level; 3-NP, 3-nitropropionic acid; AIF, apoptosis-inducing factor; cyt c, cytochrome c; DHPG, 3,5-dihydroxyphenylglycine; div, days in vitro; HD, Huntington's disease; HSP60, heat-shock protein 60; HtrA2, high temperature requirement protein A2; IMS, intermembrane space; OMM, outer mitochondrial membrane; PCD, programmed cell death; PI, propidium iodide; SIN-1, 3-morpholinosydnonimine; Smac/DIABLO, second mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Our results on cytosolic AIF level showed an increase after St and Dox treatment with a higher effect in the former model. These observations are in line with previous data demonstrating the participation of AIF translocation in the St-and Dox-evoked cell damage in various cellular systems, including neuronal cell cultures (Beart et al, 2007;Diwakarla et al, 2009;Grishchuk et al, 2011;Pucci et al, 2008;Wu et al, 2004;Yuste et al, 2005). Interestingly, we showed that the tested mGluR II/III agents attenuated the St-or Dox-evoked increase in cytosolic AIF level (Fig.…”
Section: Article In Presssupporting
confidence: 94%
See 2 more Smart Citations
“…Our results on cytosolic AIF level showed an increase after St and Dox treatment with a higher effect in the former model. These observations are in line with previous data demonstrating the participation of AIF translocation in the St-and Dox-evoked cell damage in various cellular systems, including neuronal cell cultures (Beart et al, 2007;Diwakarla et al, 2009;Grishchuk et al, 2011;Pucci et al, 2008;Wu et al, 2004;Yuste et al, 2005). Interestingly, we showed that the tested mGluR II/III agents attenuated the St-or Dox-evoked increase in cytosolic AIF level (Fig.…”
Section: Article In Presssupporting
confidence: 94%
“…Moreover, Movsesyan et al (2004) demonstrated that mGluR5 agonist, CHPG was protective against the β-amyloid-induced cell death in primary cortical neurons and that effect was connected to the inhibition of caspase-3 activity and nuclear AIF translocation induced by the used proapoptotic factor. On the other hand it has been shown that DHPG (5 mM) could evoke neuronal cell death by mechanism engaging caspase-3 and calpain activation, as well AIF nuclear translocation (Diwakarla et al, 2009).…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…The reversible complex II inhibitor malonate induces a similar pattern of injury to 3NP by a mechanism involving exacerbation of excitotoxicity. Our data in cultured striatal GABAergic neurons reveal that 3NP induces a profile of PCD more consistent with programmed necrosis with early redistribution of AIF involving activation of both calpain and caspase-3 [75]. Mutant Htt has reported effects, both NMDA-mediated and calcium-mediated, on ∆ψ m .…”
Section: Mitochondrial Respiratory Complexes Oxidative Damage and Pcdsupporting
confidence: 54%
“…However, Beclin-1 was not found to be cleaved in these neurons after STS treatment (data not shown). While caspase activity has been reported here, only a low number of neurons were scored positive for caspase-9 and -3 activity [26] relative to the total number of dead cells after 24 h. Thus, it is possible that another caspase-independent pathway to cell death may be operative within a subpopulation of STS-treated neurons [54], without involvement of Beclin 1. Overall, the differential involvement of Beclin 1 and Atg7 highlights the complexity of neuronal cell death and the significance of interaction between the different types of cell death.…”
Section: Dual Roles For Beclin 1 In Neuronal Cell Deathmentioning
confidence: 83%